2020
DOI: 10.1590/s0004-2803.202000000-64
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated With Small Intestinal Bacterial Overgrowth in Patients With Crohn’s Disease: A Retrospective Study at a Referral Center

Abstract: BACKGROUND: Small intestinal bacterial overgrowth (SIBO) appears to be common in patients with Crohn’s disease (CD). The rate of SIBO has been estimated at 25%-88% in this setting. However, different demographic, socioeconomic, and disease-related factors may exist between South American and North American or European populations that may limit the generalization of these findings, as the data are mainly derived from North American or European studies. OBJECTIVE: We studied the prevalence and predictors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
5
0
5
Order By: Relevance
“…Alternatively, the breath test, a widely used method for diagnosing SIBO, has the advantages of being simple, non-invasive and easily acceptable. Recent studies have shown that SIBO is closely associated with various diseases, including Crohn's disease [3], irritable bowel syndrome [4], functional AGING dyspepsia [5], hepatic encephalopathy [6], and nonalcoholic fatty liver disease [7].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the breath test, a widely used method for diagnosing SIBO, has the advantages of being simple, non-invasive and easily acceptable. Recent studies have shown that SIBO is closely associated with various diseases, including Crohn's disease [3], irritable bowel syndrome [4], functional AGING dyspepsia [5], hepatic encephalopathy [6], and nonalcoholic fatty liver disease [7].…”
Section: Introductionmentioning
confidence: 99%
“…We also assessed the association between SIBO and the clinical data of people with CD. Numerous investigations have observed that surgical procedures, as well as strictures or fistulae, are risk factors for the presence of SIBO in people with CD (10,16,17,20,22). We found that patients who were SIBO-positive showed higher rates of stricturing phenotypes and intestinal resection than SIBO-negative patients, although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 48%
“…Alterations in the GI microbiome occur in patients with CD. Numerous studies have suggested a link between SIBO and CD (10,(16)(17)(18)(19)(20)(21)(22)(23), but the significance of SIBO in diagnosing quiescent CD has not been extensively researched. In this study, we explored whether SIBO is associated with subsequent clinical relapse of CD.…”
Section: Discussionmentioning
confidence: 99%
“…Клинические проявления СИБР могут варьировать от отсутствия симптомов до тяжелых последствий мальабсорбции и включать диарею, метеоризм, боли в животе, дефицит витаминов, включая B 12 , железодефицитную анемии, гипоальбуминемию, потерю массы тела [1,4,5,9,[12][13][14][15][16].…”
Section: Introductionunclassified